Las utilidades del trabajador en general y su actual Limitación, vulnera derechos fundamentales de los trabajadores - Teneda Zapata, Víctor Hugo (2016)
On April 10 of this year 2015, published in Official Gazette of Ecuador, the Organic Law for Labor Justice and Labor Award in the Home. This Organic Law among others, reform various articles of the current Labour Code, specifically Article 97, which is the subject of this investigation and refers to the payment of utilities worker in general, where a limit is set to benefit profits. Among the reforms to the Labour Code, then we have to Art. 97 that was in effect on the date prior to the reform, adds the following: "Art. 97.1.- limit the distribution utilities' profit sharing distributed to the workers as I mentioned in the previous article may not exceed twenty Unified Basic salaries of workers in general. In the event that their value exceeds the prescribed amount, the balance shall be paid to the regime of solidarity Social Security benefits. The competent labor administrative authority will issue the necessary ministerial agreements for the proper implementation of what is stated in this article. Note: Article added by Article 15 of Law No. 0, published in Official Gazette Supplement 483 of April 20, 2015 (see ...)”. Analyzed this legal provision was included in the Labour Code, we see that this rule has been restricted for the benefit of workers by imposing a cap on earnings of workers in general and that they can not exceed twenty basic unified salaries worker in general, a situation that did not happen before the term of the organic law of labor law that reformed the Labour Code.